Are We Ready for New Technologies? The Relation Between Human Values and Technology Readiness Applied to M-Commerce in Brazil - Fujihara, Ricardo Ken; Montezano, Lana; Alfinito, Solange (Organizações & Sociedade, 2022)
This study describes the relation between human values and technology readiness in Brazilian mobile commerce (m-commerce). This study consisted of an online survey including the Portrait Values Questionnaire-Revised (PVQ-R), the Technology Readiness Index 2.0, and SES items in all Brazilian states (N=2,171). Our structural equation modeling showed that human values predicted technology readiness; and attitude, intention to purchase online via mobiles. Self-enhancement and openness to change positively influenced the technology readiness contributor factor, whereas self-transcendence negatively influenced the technology inhibitor factor, and conservation positively influenced it. Theoretical and managerial contributions developed a conceptual model involving human values, technology readiness, and intention to purchase online via mobiles. This study can help develop public policies related to information security, aiming to increase consumer confidence in using new technologies in m-commerce.